Standar Penilaian Pembelajaran pada Jenjang Sekolah Dasar - Aufar Sania; Ni Made Nitha Balistha; I Wayan Lasmawan; Ni Wayan Rati (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the implementation of learning assessment standards at the elementary school level at SD Negeri Hindu 1 Bukian. The research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the principal, classroom teachers, and learning assessment documents. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, which consists of data condensation, data display, and conclusion drawing and verification. The findings indicate that learning assessment standards have been implemented in accordance with the principles of the Merdeka Curriculum through diagnostic, formative, and summative assessments using both test and non-test techniques. The reporting of students' learning outcomes has been conducted transparently and accountably through report cards and continuous communication between teachers and parents. Several challenges remain, including limited time for conducting assessments, diverse student characteristics, and teachers' competence in developing assessment instruments. Strengthening teachers' professional competence and institutional support is essential to enhance the effectiveness, objectivity, and sustainability of learning assessment implementation.